2014
DOI: 10.2175/106143013x13807328849413
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Microbial Products from Water Biological Treatment Process: A Review

et al.

Abstract: The relationship between soluble microbial products (SMPs) and extracellular polymeric substances is described, and the characteristics of SMPs in the biological wastewater treatment process, including molecular weight distribution, metal-chelating property, biodegradability, biotoxicity, and membrane fouling, are investigated. The SMPs produced by autotrophs are degradable and utilizable for heterotrophs, thereby confirming the biodegradation of SMPs. Soluble microbial product models are designed through thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 92 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Soluble microbial products (SMPs) released by microorganisms during the normal metabolism in the biological process contribute to nitrogenous organics in the effluent. 12 Previous studies have identified the SRT as one of the most significant factors responsible for SMP content, 16,43,44 and nitrogenous compounds derived from SMPs readily stimulate algal growth. 7 High effluent DON bioavailability observed at long SRTs in this study may therefore be contributed by SMP-based nitrogenous organic compounds.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Soluble microbial products (SMPs) released by microorganisms during the normal metabolism in the biological process contribute to nitrogenous organics in the effluent. 12 Previous studies have identified the SRT as one of the most significant factors responsible for SMP content, 16,43,44 and nitrogenous compounds derived from SMPs readily stimulate algal growth. 7 High effluent DON bioavailability observed at long SRTs in this study may therefore be contributed by SMP-based nitrogenous organic compounds.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…In the biological treatment process, soluble microbial products (SMPs) were released by microbial degradation of organic matters through cell lysis, cell membrane diffusion, and anabolic loss accompanied (Kang et al 2014). Some relevant literature con rmed that humic substances, proteins, and carbohydrates were the dominant components of SMPs (Shen et al 2012;Cui et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Notably, dissolved organic matters (DOM) in the textile effluent, containing soluble microbial products and unknown estrogenic/ antiestrogenic chemicals, is changeable along with biological degradation and synthesis. 25,26 Therefore, DOM plays an important role in better evaluation of the estrogenic/ antiestrogenic activities of the textile dyeing wastewater.…”
Section: Introductionmentioning
confidence: 99%